Pengelolaan Program Kegiatan Keagamaan dalam Mewujudkan Visi Membentuk Lulusan Berakhlakul Karimah - Muhammad Fahri Ramdani; Nan Rahminawati; Huriah Rachmah (UPT Publikasi Ilmiah Unisba, 2025)
Abstract. One of the efforts that can be made for reduced the phenomenon of moral is through the effective management of religious activity programs. This study aims to describe the management of religious activity programs at SMAN 1 Ciasem in realizing the vision of producing graduates with noble character, focusing on the aspects of planning, implementation, and evaluation. This research uses a qualitative approach with a descriptive method. Data collection techniques were carried out through observation, in-depth interviews with the principal, PAI’s teachers, IRMA mentors, and documentation. The data were analyzed through stages of data reduction, data presentation, and conclusion drawing. The results show that the planning of religious activities is accomplished out systematically and integrated with the school’s vision, involving all school components. Program implementation is conducted routinely and in various forms, including daily activities such as congregational prayers, tahsin and tahfizh, as well as weekly and incidental activities such as Islamic holiday celebrations, and others. Evaluation is conducted in a structured manner through supervision and assessments in the annual work meetings, aiming to identify the effectiveness of the activities and design more optimal follow-up actions. In conclusion, the management of religious activity programs at SMA Negeri 1 Ciasem has been implemented effectively and has made a significant contribution in shaping the religious character of the students. Abstrak. Salah satu upaya yang dapat dilakukan untuk mengurangi fenomena kemerosotan moral di kalangan remaja adalah melalui pengelolaan program kegiatan keagamaan secara efektif. Penelitian ini bertujuan untuk mendeskripsikan pengelolaan program kegiatan keagamaan di SMAN 1 Ciasem dalam mewujudkan visi membentuk lulusan berakhlakul karimah, dengan fokus pada aspek perencanaan, pelaksanaan, dan evaluasi program. Penelitian ini menggunakan pendekatan kualitatif dengan metode deskriptif. Teknik pengumpulan data dilakukan melalui observasi, wawancara mendalam dengan kepala sekolah, guru PAI, pembina IRMA, dan dokumentasi. Data dianalisis melalui tahapan reduksi data, penyajian data, hingga penarikan kesimpulan. Hasil penelitian menunjukkan bahwa perencanaan kegiatan keagamaan dilakukan secara sistematis dan terintegrasi dengan visi sekolah, melibatkan seluruh unsur sekolah. Pelaksanaan program dilakukan secara rutin dan variatif, meliputi kegiatan harian seperti shalat berjamaah, tahsin tahfizh, hingga kegiatan mingguan dan insidental seperti perayaan hari besar Islam, dll. Evaluasi dilakukan secara terstruktur melalui pengawasan maupun penilaian pada rapat kerja tahunan, guna mengidentifikasi efektivitas kegiatan serta merancang tindak lanjut yang lebih optimal. Kesimpulannya, pengelolaan program kegiatan keagamaan di SMAN 1 Ciasem telah berjalan efektif dan memberikan kontribusi signifikan dalam membentuk karakter religius peserta didik.